(untitled) (Research, Society and Development, 2021)
The active germplasm bank (AGB) of Carapichea ipecacuanha (Brot.) L. Andersson at Embrapa Eastern Amazon, in the city of Belém, PA, was the first of its kind to be opened in Brazil for this endangered medicinal species and holds important accessions for agricultural and reproductive research, including the production of active principles. This study aimed to chemically characterize 42 accessions from that AGB by simultaneously quantifying cephaeline and emetine contents in roots using high-performance liquid chromatography with a diode-array detector (HPLC-DAD). Cephaeline concentrations ranged from ‘undetected’ to 1.76%, whereas emetine concentrations were found between 0.64% and 2.49%. The overall emetine/cephaeline ratio varied from 0.43 to 3.52. The differences among mean concentrations of alkaloids observed by comparing the Scott-Knott test at 5% probability suggest the chemical variation among the samples assessed. Therefore, it is concluded such chemical differences may favor the selection of genetic material for commercial purposes based on the production of emetine and/or cephaeline, likewise may contribute to breeding programs.